Mining geophysics - Parasnis, D. S.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier Scientific Pub. Co., 1973)
This book covers all applications of geochemistry and geophysics.
Chapter 1. The role of geophysics in ore prospecting -- chapter 2. General aspects of the collection and presentation of geophysical data -- chapter 3. Magnetic methods -- chapter 4. The self-potential method -- chapter 5. Electromagnetic methods -- chapter 6. Electrical methods -- chapter 7. Induced polarization methods -- chapter 8. Gravity methods -- chapter 9. Seismic methods -- chapter 10. Radioactive methods -- chapter 11. Airborne magnetic and electromagnetic methods -- chapter 12. Combination of geophysical methods.
Includes bibliographical references (pages 381-388).
Print version record.
Elsevier
Keywords: Prospecting -- Geophysical methods; Prospection géophysique.; TECHNOLOGY & ENGINEERING -- Mining; Prospecting -- Geophysical methods; Bergbau; Geophysik; Electronic books